2019
DOI: 10.1108/jaee-10-2018-0109
|View full text |Cite
|
Sign up to set email alerts
|

The link between CSR and earnings quality: evidence from Egypt

Abstract: Purpose The purpose of this paper is to investigate the relationship between corporate social responsibility (CSR) and earnings quality, as proxied by accrual earnings management, in Egyptian firms. This research is conducted in a bidirectional fashion using simultaneous equations and considers two theoretical perspectives. Design/methodology/approach The study employs CSR annual scores from the Egyptian environmental, social and governance index (S&P/ESG index) for the 100 highest scoring firms from 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
1
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 81 publications
9
33
1
9
Order By: Relevance
“…This result is consistent with the ethical perspective: Jordanian managers in firms with higher CSR activities are less likely to engage in REM. The findings are in line with those reporting a negative CSR-EM relationship based on discretionary accruals (Almahrog et al, 2018;Garcia-Sanchez et al, 2020;Gras-Gil et al, 20162019m2012Kumala & Siregar, 2020Mohmed et al, 2019). The current results support the moral and ethical perspective that engagement in CSR activities leads to reducing EM practices in an emerging market, Jordan.…”
Section: Corporate Social Responsibility Board Gender Diversity and supporting
confidence: 89%
See 4 more Smart Citations
“…This result is consistent with the ethical perspective: Jordanian managers in firms with higher CSR activities are less likely to engage in REM. The findings are in line with those reporting a negative CSR-EM relationship based on discretionary accruals (Almahrog et al, 2018;Garcia-Sanchez et al, 2020;Gras-Gil et al, 20162019m2012Kumala & Siregar, 2020Mohmed et al, 2019). The current results support the moral and ethical perspective that engagement in CSR activities leads to reducing EM practices in an emerging market, Jordan.…”
Section: Corporate Social Responsibility Board Gender Diversity and supporting
confidence: 89%
“…It was found that socially responsible firms are less likely to manage earnings (Almahrog et al, 2018; Y. Kim et al, 2012;Mohmed et al, 2019). Kumala and Siregar (2020) report a negative association between CSR and EM in firms listed on the Indonesia Stock Exchange.…”
Section: Corporate Social Responsibility and Real Earnings Managementmentioning
confidence: 99%
See 3 more Smart Citations